Un ‘Occidente’ sradicato. Gli usi del linguaggio classico nell’architettura di Astana, nuova capitale del Kazakistan (2001-2013) - Marcomini, Federico (Studi e ricerche di storia dell'architettura, 2025)
The article investigates the uses of classical language in the architecture of Astana, the capital of Kazakhstan since 1997. It focuses on the Presidential Palace Ak Orda (2001-2004) and the Astana Opera Theatre (2010-2013), situating them within the recent debate on the relationship between classical architecture and Western history. After an introduction covering the foundation of Astana and its architectural logics, highlighting the design activity of then-President Nursultan Nazarbayev, the article provides an overview of Mabetex Group, a construction firm active in Astana and responsible for the selected buildings. The analysis of the case studies is based on governmental and company texts, local press, museum panels, presidential speeches and an interview with Mabetex’s project manager, emphasising how a certain vision of the ‘West’ has influenced the design and promotion of these buildings, complementing (or overshadowing) local references. The data are interpreted mainly in terms of postcolonial studies, on the persistence of Western cultural influence in the globalised contemporaneity and its problematic implications. Besides a documentary reconstruction, the essay aims to critically examine the meanings behind the displacement of architectural languages in the hyper-contemporaneity, focusing on a context redefining its roots after gaining independence from Soviet Union and exploring the role of the Western architectural tradition in this process.